ANALISIS EXPENSE RATIO, FUND SIZE, TINGKAT RISIKO DAN PORTOFOLIO TURNOVER TERHADAP KINERJA REKSA DANA SAHAM - Fenni Anggriani; Nailal Husna (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2019)
This research aims at analyzing the influence of expense ratio, fund size,risk level and portofolio turnover on the mutual stock funds registered in Bursa Efek Indonesia (BEI) period2014 – 2017. The sampling technique of this research is the full sampling where all population becomes samples, which include 16 companies. The method analysis used to see factors influencing the mutual stock funds is multiple regretion linear with a test T to test the hypothesis. This research finds out that the risk level does influence the mutual stock fund, while expense ratio, fund size and portofolio turnover don’t.